2013
DOI: 10.2147/jaa.s25415
|View full text |Cite
|
Sign up to set email alerts
|

Extrafine inhaled corticosteroid therapy in the control of asthma

Abstract: Small airways disease plays an important role in the pathogenesis of asthma, but assessment of small airways impairment is not easy in everyday clinical practice. The small airways can be examined by several invasive and noninvasive methods, most of which can at present be used only in the experimental setting. Inhalers providing extrafine inhaled corticosteroid particle sizes may achieve sufficient deposition in the peripheral airways. Many studies have reported the beneficial effects of extrafine inhaled cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 88 publications
(114 reference statements)
0
5
0
Order By: Relevance
“…Evidence is accumulating to support a distinct, “small aiways”, clinical phenotype for patients with uncontrolled asthma who have impaired small airway function and conventional measures of pulmonary function in the normal range [58]. There is also suggestive evidence that, in some “clinical” asthma phenotypes, the small airways are more affected, including nocturnal asthma, severe steroid-dependent or difficult-to-treat asthma, asthma complicated by smoking, elderly asthmatic patients and those with fixed airflow obstruction, and asthmatic children [147, 148]. Taken together, these findings support the view that distal lung is a very important target in any therapeutic strategy for effective treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence is accumulating to support a distinct, “small aiways”, clinical phenotype for patients with uncontrolled asthma who have impaired small airway function and conventional measures of pulmonary function in the normal range [58]. There is also suggestive evidence that, in some “clinical” asthma phenotypes, the small airways are more affected, including nocturnal asthma, severe steroid-dependent or difficult-to-treat asthma, asthma complicated by smoking, elderly asthmatic patients and those with fixed airflow obstruction, and asthmatic children [147, 148]. Taken together, these findings support the view that distal lung is a very important target in any therapeutic strategy for effective treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these findings support the view that distal lung is a very important target in any therapeutic strategy for effective treatment. The randomized clinical trials reported to date show that the extrafine and nonextrafine ICS formulations have similar efficacy in terms of primary endpoints; however the availability of small-particle aerosols enables a higher drug deposition into the peripheral lung [102104] and potentially provides additional clinical benefits compared with large-particle treatment [147]. In several studies a better small-airways response to treatment with montelukast [142144] or extrafine-particle ICSs [111113] and ICS/LABA combination [128132] is accompanied by better asthma control.…”
Section: Discussionmentioning
confidence: 99%
“…Small airways seem to be affected more in certain phenotypes, as nocturnal asthma, severe steroid-dependent or difficult-to-treat asthma, asthma complicated by smoking, elderly asthmatic patients and/or patients with fixed airflow obstruction. In these cases, the use of ICS in extra-fine particles with higher deposition rates on the periphery of the airways may be more effective than the use of traditional ICS [62]. …”
Section: Introductionmentioning
confidence: 99%
“…Using drugs with different mechanisms of action could result in additive effects in reversing resistance to corticosteroids [62]. The role of ICS in extra-fine particles + LABA associated with anti-leukotrienes in asthmatic smokers has not been published.…”
Section: Introductionmentioning
confidence: 99%
“…The small airways play a role in the pathobiology of asthma and, although they are involved in half of all cases of asthma, they can have a distinct role in specific disease phenotypes [1317]. …”
Section: Introductionmentioning
confidence: 99%